Family firm a distinctive form of organization - Micelotta, Evelyn ca. 20./21. Jh; Benedetti, Carlotta ca. 20./21. Jh; Rovelli, Paola ca. 20./21. Jh (Cambridge elements, 2023)
This title reinvigorates calls to explore avenues to research on organization theory and family business in three areas: hybridity, paradoxes, and temporality